High antimony resistance strain Enterobacter sp. Z1 mediates biomineralization of antimony trioxide - Zijie Zhou; Hongbo Yu; Gejiao Wang; Mingshun Li; Kaixiang Shi (Environment International)
The increasing antimony (Sb) contamination prevalence poses a concern owing to its toxicity and potential carcinogenic properties. However, mechanisms underlying the microbial conversion of soluble Sb into insoluble Sb minerals remain unclear. In the present study, Enterobacter sp. Z1 strain demonstrated remarkable resistance to antimony potassium tartrate [Sb(III)] (>250 mM) in R2A medium. Furthermore, Enterobacter sp. Z1 produced antimony trioxide (Sb2O3) via biomineralization during cultivation. Omics analysis revealed the upregulation of pyruvate metabolism and accumulation of DL-3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) in the presence of Sb(III).Using pyruvate as the sole carbon source in a chemically defined medium significantly enhanced Sb(III) biomineralization ratio from 20.8 % to 90.4 % compared with that using R2A medium. Additionally, reduced Sb(III) biomineralization and intracellular pH levels were observed following aceE gene knockout in Enterobacter sp. Z1. However, this impaired phenotype was rescued by complementing the aceE gene or introducing purified AceE into the bacterial lysates. Notably, AceE exhibited binding affinity for Sb(III). Our findings revealed the pyruvate–HMG-CoA pathway as the mechanism underlying Sb biomineralization, facilitating the release of Sb ions from tartrate and maintaining intracellular pH stability, thereby catalyzing Sb2O3 synthesis. This study provides insights into the Sb biogeochemical cycle.